Silica nanoparticles induce caspase-dependent apoptosis through reactive oxygen species-activated endoplasmic reticulum stress pathway in neuronal cells. (March 2020) - Lee, Kuan-I; Lin, Jhe-Wei; Su, Chin-Chuan; Fang, Kai-Min; Yang, Ching-Yao; Kuo, Chun-Ying; Wu, Chin-Ching; Wu, Cheng-Tien; Chen, Ya-Wen
Abstract: Human exposure to silica nanoparticles (SiNPs) has been widely applied as vehicles for drug delivery and cellular manipulations in nanoneuromedicine. SiNPs may cause adverse effects in the brain, but potential mechanisms underlying SiNPs-induced neurotoxicity are remained unclear. Here, we examined cytotoxic effects and the cellular mechanisms of SiNPs-induced neuronal cell death. In this study, the results showed that SiNPs significantly decreased cell viability and induced apoptosis in Neuro-2a cells as evidenced by the increase caspase-3 activity and the activation of caspase cascades and poly (ADP-ribose) polymerase (PARP). In addition, endoplasmic reticulum (ER) stress was triggered as indicated by several key molecules including glucose-regulated protein (GRP)78 and 94, C/EBP homologous protein (CHOP), activation transcription factor (ATF)-4, and caspase-12. Pretreatment of Neuro-2a cells with specific pharmacological inhibitor of ER stress (4-phenylbutyric acid (4-PBA)) effectively alleviated the SiNPs-induced ER stress and apoptotic related signals. Furthermore, 2′, 7′-Dichlorofluorescein fluorescence as an indicator of reactive oxygen species (ROS) formation after exposure of Neuro-2a cells to SiNPs significantly increased ROS levels. Antioxidant N -acetylcyseine (NAC) effectively reversed SiNPs-induced cellular responses. Taken together, these results suggest that SiNPs exposure exerts its neurotoxicity in cultured neuronal cells by inducing apoptosis via a ROS generation-activated downstream ER stress signaling pathway. Highlights: Silica nanoparticles (SiNPs) induced neuronal cell death underwent apoptosis. SiNPs induced ER stress-triggered neuronal cell apoptosis. ROS-activated ER stress signals involved in SiNPs-induced neurotoxicity.